An alternative analysis of indirect tensile test results for evaluating fatigue characteristics of asphalt mixes. (30th March 2018) - Barman, Manik; Ghabchi, Rouzbeh; Singh, Dharamveer; Zaman, Musharraf; Commuri, Sesh
Highlights: Asphalt mixes shall be screened based on their fatigue resistance. Use of ITS test results for fatigue characterization may be the easiest. Fatigue index can discriminate the mixes based on the fatigue resistance. Fatigue index correlates well with SCB test results. Abstract: Fatigue cracking is one of the major distresses responsible for the failure of asphalt pavements. The widely-accepted Superpave® volumetric mix design method does not consider screening the asphalt mixes based on their fatigue resistance. Based on a survey conducted in this study, it was found that many state Departments of Transportations (DOTs) do not perform a fatigue test during mix design, mainly due to lack of specialized equipment, trained personnel and consensus about the most appropriate test method. This present study was undertaken to suggest a simple, quick and effective fatigue test method and the corresponding data analysis procedure. It was found that the indirect tension test, which is usually conducted in the DOTs on a regular basis, can be used to characterize the fatigue resistance of asphalt mixes as well. A simplified data analysis approach has been proposed. The fatigue resistance of asphalt mixes can be determined by using a newly derived parameter called Fatigue Index (fi ). Fatigue resistance of five different asphalt mixes were evaluated using this new parameter, fi . It was found that the fi parameter were able to statistically discriminate five selected asphalt mixes with respect to their fatigue resistance. The effectiveness of the fi parameter was verified by investigating its correlations with the results of the semi-circular bend and four-point beam fatigue test results.